Factors Predicting Immunosuppressive Medication Adherence in Kidney Transplant Persons - Pramote, Nantakorn; Ua-Kit, Noraluk (Journal of The Royal Thai Army Nurses, 2025)
This predictive correlational study aims to examine adherence to immunosuppressive medication (ISM) and the predictive factors influencing ISM adherence among kidney transplant persons. The study sample consists of 113 kidney transplant persons, aged 18 years and older, from the Kidney Transplant Clinic in a tertiary-level government hospitals in Bangkok. Data are collected by using eight questionnaires, including: Demographic data questionnaire, ISM questionnaire, comorbidity questionnaire, social support questionnaire, perceived susceptibility to kidney rejection questionnaire, perceived severity of kidney rejection questionnaire, perceived benefits of ISM questionnaire, and perceived barriers to ISM questionnaire. The results revealed that: 1) The participants demonstrated a high level of ISM adherence, with an average score of 23.09 (SD = 0.84). 2) The predictive factors influencing to ISM adherence among kidney transplant persons included time after transplantation, social support, perceived barriers to ISM, and perceived susceptibility of kidney rejection. These factors account for 31.40% of the variance in ISM adherence among kidney transplant persons (Adjusted R² = 0.314, p < .05).